Instagram: A social media tool to strengthen and supplement the delivery of medical education - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Medical Journal of Babylon, 2022)
The process of transforming young students into competent medical graduates is a challenging one, wherein as teachers, we have to adopt a combination of innovative and traditional teaching-learning approaches to meet the needs of different types of learners. In the current era, the majority of teachers and medical students has access to the Internet and use smartphones. Instagram is a social media application that provides a platform for users to share image-based or video-based information. The findings of studies have revealed that the application has been utilized by teachers to share images dealing with infectious diseases and radio-diagnosis, and this, in turn, inculcates clinical reasoning and critical thinking skills. To conclude, the utility and reach of social media applications, including Instagram, are increasing among medical students each day. The need of the hour is to acknowledge the scope of the same and use the same for the benefit of students either in the form of passing specific information or through a structured curriculum to ensure attainment of the learning outcomes.